Excavations at Garnhall on the line of the Antonine Wall - Woolliscroft, David J (Proceedings of the Society of Antiquaries of Scotland, 2009)
Excavations at Garnhall, Cumbernauld, revealed a number of features associated with a reasonably well-preserved section of the Antonine Wall. These included a series of pits on the berm between the Wall and its ditch, parts of a temporary camp, a stone platform attached to the Wall rampart back and what may be a Roman watch tower in an ideal position to act as an observation post and a signalling link between the Wall forts of Westerwood and Castlecary. The work was carried out by volunteers and students of the Universities of Manchester, Freiburg and Edinburgh, under the direction of the writer, assisted by Dr B Hoffmann.